Cervical lymph node metastasis in adenoid cystic carcinoma of oral cavity and oropharynx: A collective international review. Issue 5 (October 2016) - Suárez, Carlos; Barnes, Leon; Silver, Carl E.; Rodrigo, Juan P.; Shah, Jatin P.; Triantafyllou, Asterios; Rinaldo, Alessandra; Cardesa, Antonio; Pitman, Karen T.; Kowalski, Luiz P.; Robbins, K. Thomas; Hellquist, Henrik; et al.
Abstract: The purpose of this study was to suggest general guidelines in the management of the N0 neck of oral cavity and oropharyngeal adenoid cystic carcinoma (AdCC) in order to improve the survival of these patients and/or reduce the risk of neck recurrences. The incidence of cervical node metastasis at diagnosis of head and neck AdCC is variable, and ranges between 3% and 16%. Metastasis to the cervical lymph nodes of intraoral and oropharyngeal AdCC varies from 2% to 43%, with the lower rates pertaining to palatal AdCC and the higher rates to base of the tongue. Neck node recurrence may happen after treatment in 0–14% of AdCC, is highly dependent on the extent of the treatment and is very rare in patients who have been treated with therapeutic or elective neck dissections, or elective neck irradiation. Lymph node involvement with or without extracapsular extension in AdCC has been shown in most reports to be independently associated with decreased overall and cause-specific survival, probably because lymph node involvement is a risk factor for subsequent distant metastasis. The overall rate of occult neck metastasis in patients with head and neck AdCC ranges from 15% to 44%, but occult neck metastasis from oral cavity and/or oropharynx seems to occur more frequently than from other locations, such as the sinonasal tract and major salivary glands. Nevertheless, the benefit of elective neck dissection (END) in AdCC is not comparable to that of squamous cell carcinoma, because the main cause of failure is not related to neck or local recurrence, but rather, to distant failure. Therefore, END should be considered in patients with a cN0 neck with AdCC in some high risk oral and oropharyngeal locations when postoperative RT is not planned, or the rare AdCC-high grade transformation.